2011
DOI: 10.1590/s1984-29612011000300016
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Toxoplasma gondii infection in cats from Curitiba, Paraná, Brazil

Abstract: Toxoplasmosis is a worldwide zoonosis caused by the protozoa Toxoplasma gondii which infects all warm-blood vertebrates. This study aimed to assess the seroprevalence of anti-Toxoplasma gondii antibodies in a population of domestic cats seen at a major cat-only veterinary clinic in Curitiba, Paraná State, Southern Brazil. Serum samples were processed by indirect immunofluorescence assay (IIFA) for the detection of IgG. Antibody titers were found in 16.3% (46/282) of sera analyzed, with titers to T. gondii of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 7 publications
2
4
1
1
Order By: Relevance
“…However, this difference was not observed by Rosa et al (2010) or Garcia et al (1999). In a survey of 282 cats in the city of Curitiba, Paraná, Cruz et al (2011) reported that there was no difference between positive and negative cats in terms of sex and age (p > 0.05), which corroborates the results obtained in Rio Branco, Acre.…”
Section: Resultssupporting
confidence: 81%
“…However, this difference was not observed by Rosa et al (2010) or Garcia et al (1999). In a survey of 282 cats in the city of Curitiba, Paraná, Cruz et al (2011) reported that there was no difference between positive and negative cats in terms of sex and age (p > 0.05), which corroborates the results obtained in Rio Branco, Acre.…”
Section: Resultssupporting
confidence: 81%
“…Cats acquire the infection by hunting rats and birds 5 . However, a previous study with domiciled cats in Curitiba showed a seroprevalence of 16.3% for T. gondii, despite no association with hunting and/or outdoor access 17 . These results corroborate the low prevalence found in this study, indicating that rats may not be the main source of T. gondii infection in domestic cats.…”
mentioning
confidence: 70%
“…Seropositivity rates in cats in this study were not significantly associated with their age. However, Cruz et al (2011) reported a prevalence of 16.3% (46/282) among healthy house cats from veterinary clinics in Curitiba, Paraná, and found that seropositivity rates tended to increase with age, an observation also reported by Garcia et al (1999). These findings are likely explained by increased exposure to different sources of infection and routes of transmission throughout their lives (LUCAS et al, 1999).…”
Section: Resultsmentioning
confidence: 99%